Pemodelan Analisis Rantai Markov untuk Mengestimasi Potensi Kasus Narkoba di Indonesia - Bagaskoro Cahyo Laksono; Nucke Widowati Kusumo Projo (Politeknik Statistika STIS, 2021)
Drug abuse not only threatens the survival and future of the abuser, but also the future of the nation and state. For this reason, up-to-date information is needed regarding the severity of drug abuse, including through recording the number of drug cases. This study aims to analyze the potential for drug cases in six provinces with the highest number of reported drug cases in Indonesia, namely North Sumatra, Jambi, Bali, Central Kalimantan, South Kalimantan and East Kalimantan. The methodology used in this research is descriptive analysis and Markov chain analysis. The results of the estimation of the number of drug cases in five years, from 2019 to 2023, show that East Kalimantan Province is the province with the most drug cases. Then followed by North Sumatra, Bali, South Kalimantan, Central Kalimantan, and Jambi.